Stable matching with double infinity of workers and firms - Fuentes, Matías Nicolás. (2018)
In this paper we analyze the existence of stable matchings in a two- sided large market in which workers are assigned to firms. The market has a continuum of workers while the set of firms is countably infinite. We show that, under certain reasonable assumptions on the preference correspondences, stable matchings not only exist but are also Pareto optimal.